Implementasi Green Building pada Gedung Perpustakaan UIN Malang sebagai Upaya Pengabdian untuk Masyarakat - Fitriani, Fitriani; Zuliana, Eni (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2024)
The Climate change occurs periodically and quite dramatically, one of the factors causing climate change is global warming caused by the many buildings that ignore the Green Building concept. This study examines one of the buildings in the UIN Malang area, namely the K.H Abdurrahman Wahid building which functions as a library building. To analyze efforts to apply the concept of Green Building in a library building using the principle of the Green Building Council Indonesia (GBCI) which has 6 standard assessment criteria that must be met. The research method used in this research is descriptive qualitative.After being analyzed based on the 6 criteria of the Green Building Council Indonesia UIN Malang library building gets a point of 40 and if it is realized in percentage it becomes 38,991% which is included in the silver category. To raise the ranking from silver to platinum requires 33 points with the effort to meet and maximize the categories that have been set in accordance with the predetermined GBCI rules. Keywords: GBCI, Green Building, UIN Malang Library Building, Silver